The Influence of WARTA Learning Media on Students' Critical Thinking Skills in Social Studies Learning - Nurdiansyah; Muhammad Nurfitrian; Dzulfa Nur Firdaus (Journal of Educational Studies, 2026)
Students' low critical thinking skills, especially in social studies learning. The still-low number of teachers who use various interactive learning media leads to social studies being seen as boring and not requiring critical thinking. Based on this, it is important to conduct research on how to improve students' critical thinking skills through appropriate learning media that align with the characteristics of social studies learning. Among the various interactive learning media available, one is WARTA. Given these two crucial problems, it is important to conduct research to obtain empirical, comprehensive data on the effect of WARTA learning media on students' critical thinking skills in social studies. This research uses a quantitative method with a pre-experimental model of a one-group pretest-posttest design. Data were collected via a 5-item essay test (validity r=0.62, reliability 0.77), analyzed using Shapiro-Wilk for normality, homogeneity, paired t-test (t=-7.339, p<0.001), regression (p<0.001, R²=0.757), and N-gain 0.63 (quite effective). The results showed a 75% increase in students' critical thinking skills during social studies learning. The use of WARTA Media has proven effective as an interactive cognitive stimulant for social studies learning in the digital era.